Use of 5-Fluorouracil-Soaked Bioamniotic Membranes in Trabeculectomy for Primary Open-Angle Glaucoma: A Retrospective Analysis - Chenming Zhang; Min Wu; Jianrong Wang; Miaomiao Zhang; Xu Wang; Wei Liu (Journal of Ophthalmology)
The study is a retrospective analysis of 51 patients (76 eyes) with primary open-angle glaucoma (POAG) who admitted to our hospital from 2008 to 2010 to analyze the efficacy of trabeculectomy in combination with 5-fluorouracil- (5-FU-) soaked amniotic membranes for the treatment of POAG patients. Among them, 30 patients (41 eyes) were treated with trabeculectomy in combination with 5-FU-soaked amniotic membrane and 21 patients (35 eyes) were treated with trabeculectomy in combination with MMC. Preoperative and postoperative intraocular pressures (IOP), cup/disc ratio, visual acuity and postoperative macular OCT, complications, treatment, and number of corneal endothelial cells were measured, recorded, and analyzed. At the end of 2 years of follow-up, IOP of 36 (87.8%) eyes of patients in the 5-FU group and IOP of 28 (80%) eyes of patients in the MMC group were ≤21 mmHg and patients in the 5-FU group had more stable IOP than patients in the MMC group. During the two years of follow-up, the visual acuity of 22 (53.7%) eyes in the 5-FU group remained unchanged or even improved. Trabeculectomy in combination with 5-FU-soaked biological amniotic membranes can be a surgical option for POAG patients.